Illness‐related intrusive thoughts and illness anxiety disorder. (20th January 2020) - Arnáez, Sandra; García‐Soriano, Gemma; López‐Santiago, Jose; Belloch, Amparo
Abstract : Introduction: Intrusive thoughts about health threats (illness‐ITs) are a potential cognitive risk factor for the development and maintenance of illness anxiety disorder (IAD). This study analyzes the dimensionality of illness‐ITs from normalcy to psychopathology, and it evaluates whether the appraisals instigated by the Its mediate between these thoughts and IAD symptoms. Methods: Two groups of individuals participated in the study and completed the Illness Intrusive Thoughts Inventory and the Whiteley Index. The first group was composed of 446 non‐clinical community participants. Of them, 264 individuals (68.6% women; M age  = 30.03 [ SD  = 13.83]) reported having experienced an upsetting illness‐IT in the past three months and were then included in the main analyses. The second group included 31 patients with a current main diagnosis of IAD based on DSM‐5 criteria (51.6% women; M age  = 32.74 [ SD  = 9.69]). Their severity was assessed with the Hypochondriasis Yale‐Brown Obsessive‐Compulsive Scale ‐Modified version, with scores ranging from 15 to 58 ( M  = 46.12, SD  = 9.41). Results: Illness‐ITs are common in both non‐clinical individuals and in patients with IAD, and they instigate dysfunctional emotional, cognitive, and behavioral consequences, although with greater intensity in patients than in non‐clinical individuals. The relationship between illness‐ITs and IAD is mediated by overestimation of threat and thought‐action fusion‐probability appraisals. Conclusion: Illness‐ITs are a dimensional cognitive experience. The way they are appraised facilitates their escalation into symptoms of IAD. Practitioner points: Provides support for the cognitive explanatory model of IAD and its usefulness in clinical practice. Indicates that the way people interpret and react to naturally occurring intrusive thoughts about illness seems to be a vulnerability marker for developing an illness anxiety disorder. Emphasizes that the meaning that patients with IAD ascribe to their intrusive thoughts about illnesses must be a main target in the cognitive‐behavioral treatment of IAD. Suggests that the importance of intrusive thoughts in IAD does not lie in the frequency with which they are experienced, but in the way, they are appraised/interpreted, which is what determines whether they become a clinically significant symptom. Indicates that the relationship between illness intrusive thoughts and IAD symptoms in non‐clinical individuals is based on: overestimating the negative consequences of experiencing an illness intrusive thought; and the appraisal that having such a thought would increase its likelihood of coming true. Shows that the frequency of illness‐related intrusive cognitions is associated with worse cognitive and behavioral consequences.